2014
DOI: 10.1103/physrevc.90.024327
|View full text |Cite
|
Sign up to set email alerts
|

α-cluster structure ofO18

Abstract: Background: Clustering phenomena in N = Z nuclei provide an opportunity to understand the interplay between cluster and nucleon degrees of freedom. Purpose:To study resonances in the 18 O spectrum, populated in 14 C+α elastic scattering.Method: The Thick Target Inverse Kinematics (TTIK) technique was used to measure the excitation function for the 14 C+α elastic scattering. A 42 MeV 14 C beam was used to populate states of excitation energy up to 14.9 MeV in 18 O. The analysis was performed using a multi-level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 65 publications
20
65
1
Order By: Relevance
“…Otherwise, the calculated energy spectrum is consistent with the recent experimental findings. These encouraging results, as well as other successful applications of the CNCIM to heavier nuclei [10,11], compel us to make predictions and to take part in discussions related to interpretation of recent experimental data. The α decay widths predicted by CNCIM are summarized in the fourth column of Tab.…”
Section: Study Of 10 Bementioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, the calculated energy spectrum is consistent with the recent experimental findings. These encouraging results, as well as other successful applications of the CNCIM to heavier nuclei [10,11], compel us to make predictions and to take part in discussions related to interpretation of recent experimental data. The α decay widths predicted by CNCIM are summarized in the fourth column of Tab.…”
Section: Study Of 10 Bementioning
confidence: 99%
“…[10,11]. An important property of the new SFs is that they are normalized in that the sum of all SFs for a given partial wave l and to a particular daughter state equals to the number of channels involved.…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments [29,30,17] show that broad alpha-decaying states saturating the continuum coupling strength survive even in non self-conjugate (N = Z) nuclei such as 10 Be and 18 O, where extra valence nucleons make manybody dynamics extremely complex and permit multiple other open channels.…”
Section: Rotational Bands In 10 Bementioning
confidence: 99%
“…The data for 10 Be are taken from [16] and for 18 O from [17] continuum. In addition, many recent experiments [15,17,18] have demonstrated that cluster configurations remain intact despite being embedded in complex many-body dynamics. Cluster bands extend far into continuum and involve extremely broad states that do not share the alpha decay strength with the dense spectrum of other many-body states.…”
Section: Search For Superradiance In Atomic Nucleimentioning
confidence: 99%